Improving collaboration between primary care and mental health services. (26th November 2019) - Kates, Nick; Arroll, Bruce; Currie, Elizabeth; Hanlon, Charlotte; Gask, Linda; Klasen, Henrikje; Meadows, Graham; Rukundo, Godfrey; Sunderji, Nadiya; Ruud, Torleif; Williams, Mark
Abstract: Objective: Previous guidelines and planning documents have identified the key role primary care providers play in delivering mental health care, including the recommendation from the WHO that meeting the mental health needs of the population in many low and middle income countries will only be achieved through greater integration of mental health services within general medical settings. This position paper aims to build upon this work and present a global framework for enhancing mental health care delivered within primary care. Methods: This paper synthesizes previous guidelines, empirical data from the literature and experiences of the authors in varied clinical settings to identify core principles and the key elements of successful collaboration, and organizes these into practical guidelines that can be adapted to any setting. Results: The paper proposes a three-step approach. The first is mental health services that any primary care provider can deliver with or without the presence of a mental health professional. Second is practical ways that effective collaboration can enhance this care. The third looks at wider system changes required to support these new roles and how better collaboration can lead to new responses to respond to challenges facing all mental health systems. Conclusions: This simple framework can be applied in any jurisdiction or country to enhance the detection, treatment, and prevention of mental health problems, reinforcing the role of the primary care provider in delivering care and showing how collaborative care can lead to better outcomes for people with mental health and addiction problems.